Frequency and Prognostic Impact of CDKN2A/B Alteration in Oligodendrogliomas: Systematic Review and Meta-analysis - Satoshi NAKASU; Shoichi DEGUCHI; Yoko NAKASU (Neurologia Medico-Chirurgica)
Isocitrate dehydrogenase (IDH)-mutant astrocytomas with homozygous deletion of cyclin-dependent kinase 2A/B (CDKN2A/B-HomoD) are categorized to grade 4 in the new World Health Organization (WHO) classification. However, the clinical implications of CDKN2A/B-HomoD in oligodendrogliomas remain unclear. This study systematically reviewed and meta-analyzed the literature on molecularly defined oligodendrogliomas (mOlig) to find the frequency and prognostic significance of CDKN2A/B gene alterations. Overall survival was worse in patients with CDKN2A/B-HomoD [pooled hazard ratio (pHR) 2.44; 95% confidential interval (CI), 1.59-3.76; P < 0.0001; 7 studies, 1,012 patients] than in those without CDKN2A/B-HomoD. Although the frequency (95% CI) was very low in grade 2 tumors (0.31%; 0.02-0.4) than in grade 3 tumors (9.4%; 6.2-14.0; I2 = 52.0%), pHR of multivariate analyses with covariates of WHO grade and age was still significant (P = 0.017). In contrast, the method in CDKN2A/B evaluation was a significant factor for the heterogeneity in frequency. The pooled frequency of CDKN2A/B-HomoD in grade 3 mOlig by fluorescence in situ hybridization (FISH) (20.3%) was higher than that by other methods (7.3%; P < 0.0006), probably due to the lower threshold for CDKN2A/B-HomoD in FISH studies that was used in this analysis. The frequency (95% CI) of other alterations of the CDKN2A/B gene, i.e., mutation, hemizygous deletion, and promoter methylation, was estimated as 1.48% (0.6-3.5), 15.9% (9.8-24.7), and 20.6% (13.7-29.8), respectively. The clinical significance of these alterations remains unclear due to the immaturity of the investigations.